Antimycoplasmal Activities of Compounds from Solanum aculeastrum and Piliostigma thonningii against Strains from the Mycoplasma mycoides Cluster - Kama-Kama, Francisca; Omosa, Leonidah K.; Nganga, Joseph; Maina, Naomi; Osanjo, Georges; Yaouba, Souaibou; Ilias, Muhammad; Midiwo, Jacob; Naessens, Jan (Frontiers in Pharmacology, 2017)
Abstract Infections caused by Mycoplasma species belonging to the ‘mycoides cluster’ negatively affect the agricultural sector through losses in livestock productivity. These Mycoplasma strains are resistant to many conventional antibiotics due to the total lack of cell wall. Therefore there is an urgent need to develop new antimicrobial agents from alternative sources such as medicinal plants to curb the resistance threat. Recent studies on extracts from Solanum aculeastrum and Piliostigma thonningii revealed interesting antimycoplasmal activities hence the motivation to investigate the antimycoplasmal activities of constituent compounds. The CH2Cl2/MeOH extracts from the berries of S. aculeastrum yielded a new β-sitosterol derivative (1) along with six known ones including; lupeol (2), two long-chain fatty alcohols namely undecyl alcohol (3) and lauryl alcohol (4); two long-chain fatty acids namely; myristic acid (5) and nervonic acid (6) as well as a glycosidic steroidal alkaloid; (25R)-3β-{O-α-L-rhamnopyranosyl-(1→2)-O-[α-L-rhamnopyranosyl-(1→4)]-β-D-glucopyranosyloxy-22α-N-spirosol-5-ene (7) from the MeOH extracts. A new furan diglycoside, (2,5-D-diglucopyranosyloxy-furan) (8) was also characterized from the CH2Cl2/MeOH extract of stem bark of P. thonningii. The structures of the compounds were determined on the basis of spectroscopic evidence and comparison with literature data. Compounds 1, 3, 4, 7 and 8 isolated in sufficient yields were tested against the growth of two Mycoplasma mycoides subsp. mycoides (Mmm), two M.mycoides. capri (Mmc) and one M. capricolum capricolum (Mcc) using broth dilution methods, while the minimum inhibitory concentration (MIC) was determined by serial dilution. The inhibition of Mycoplasma in vitro growth was determined by the use of both flow cytometry (FCM) and color change units (CCU) methods. Compounds 4 and 7 showed moderate activity against the growth of Mmm and Mmc but were inactive against the growth of Mcc. The lowest MIC value was 50 μg/ml for compound 7 against Mmm. The rest of the compounds showed minimal or no activity against the strains of Mycoplasma mycoides tested. This is the first report on the use of combined FCM and CCU to determine inhibition of in vitro growth of Mycoplasma mycoides. The activity of these compounds against other bacterial strains should be tested and their safety profiles determined.